2020
DOI: 10.1021/acsami.0c09562
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Difluorophosphate as an Electrolyte Additive for Potassium-Ion Batteries

Abstract: The limited cyclability and inferior Coulombic efficiency of graphite negative electrodes have been major impediments to their practical utilization in potassium-ion batteries (PIBs). Herein, for the first time, potassium difluorophosphate (KDFP) electrolyte additive is demonstrated as a viable solution to these bottlenecks by facilitating the formation of a stable and K +-conducting solid-electrolyte interphase (SEI) on graphite. The addition of 0.2 wt% KDFP to the electrolyte, results in significant improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 53 publications
2
53
0
Order By: Relevance
“…This is attributed to the decomposition of the DFP anion, which facilitates the formation of a more conductive SEI layer on the surface of HC electrodes. 38,42 Moreover, XPS peaks after 500 cycles with 1% NaDFP suggested that the contribution of P-O bonds in O 1s and P 2p became larger after 500 cycles compared to those after 20 cycles, indicative of robust SEI formation by NaDFP on HC during cycle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is attributed to the decomposition of the DFP anion, which facilitates the formation of a more conductive SEI layer on the surface of HC electrodes. 38,42 Moreover, XPS peaks after 500 cycles with 1% NaDFP suggested that the contribution of P-O bonds in O 1s and P 2p became larger after 500 cycles compared to those after 20 cycles, indicative of robust SEI formation by NaDFP on HC during cycle.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, electrolytes containing LiDFP and KDFP additives were found to form SEI layers comprising POx species, which improved interfacial properties and reduced the overpotential of graphite electrodes during cycling. [39][40][41][42][43] Despite their efficacy in LIBs and PIBs systems, this class of materials remains underexplored in SIBs.…”
Section: Introductionmentioning
confidence: 99%
“…Reproduced with permission. [ 214 ] Copyright 2020, American Chemical Society. f) The molecular structure of TMP and DTD.…”
Section: Solid Electrolyte Interface In Carbon Anodesmentioning
confidence: 99%
“…[213] The moderate addition of FEC in ester electrolyte resulted in abundant inorganic KF on the electrode surface, which enabled blocking of the infiltration of the solvent molecules to promise the cycling stability of the batteries (Figure 18a,b). Yang et al further developed a novel electrolyte additive, [214] called potassium difluorophosphate (KDFP). The small addition amount of 0.2%KDFP greatly improved the K storage kinetics, capacity retention (Figure 18c), and average Coulombic efficiency (Figure 18d) of the K/graphite cell, which was due to the formation of stable and K + -conductive SEI (Figure 18e) on the graphite anode in EC/DEC electrolyte by addition of KDFP.…”
Section: Electrolyte Additivementioning
confidence: 99%
“…Fluorine-based additives are employed in commercial LIBs for enhancing the stability of interfacial films. Difluorophosphate salts are used in K-ion batteries for remodeling the electrolyte chemistry to create a stable SEI framework [449]. Polymer additives and binders are utilized in K-ion batteries to significantly advance the molecular adhesion between the electrode-electrolyte interfaces and increase the rated capacity.…”
Section: Optimizing Solvent Formulationsmentioning
confidence: 99%